2018
DOI: 10.1007/s10826-018-1050-3
|View full text |Cite
|
Sign up to set email alerts
|

Dimensionality and Measurement Invariance of a Brief Form of the Young Schema Questionnaire for Adolescents

Abstract: The current work aims to develop and examine the psychometric properties of the Brief form of the Young Schema Questionnaire for Adolescents (B-YSQ-A), so that Early Maladaptive Schemas can be accurately measured in younger populations. Early Maladaptive Schemas are self-defeating core themes underlying maladaptive cognition, affect, and behavior. A community sample of 877 adolescents, aged 12 to 18 years old, filled out self-report instruments on maladaptive schemas, anger management, and internalizing and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 29 publications
1
8
0
5
Order By: Relevance
“…The instrument presented 433Contextos Clínicos, v. 13, n. 2, mai./ago. 2020 good internal consistency in the validation study for Brazilian adolescents(Patias et al, 2016): depression (0.90), anxiety (0.83) and stress (0.86), and in the current study, Cronbach's alphas in the subscales were: depression (0.88), anxiety (0.81), and stress (0.86).Brief Form of the Young Schema Questionnaire for Adolescents (B-YSQ-A, PortugueseVersion ofSantos, Vagos, & Rijo, 2018, validated for Brazil by Borges, Vagos, Dell'Aglio, & Rijo, 2020, which evaluates the 18 maladaptive initial schemas, based on the model proposed by Schema-Focused Therapy, using 52 items presented in a non-consecutive way which are answered based on a six-point Likert scale. The mean responses to the items assessing each of the 18 EMSs are taken as an indicator of the salience of each of these EMSs themselves.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…The instrument presented 433Contextos Clínicos, v. 13, n. 2, mai./ago. 2020 good internal consistency in the validation study for Brazilian adolescents(Patias et al, 2016): depression (0.90), anxiety (0.83) and stress (0.86), and in the current study, Cronbach's alphas in the subscales were: depression (0.88), anxiety (0.81), and stress (0.86).Brief Form of the Young Schema Questionnaire for Adolescents (B-YSQ-A, PortugueseVersion ofSantos, Vagos, & Rijo, 2018, validated for Brazil by Borges, Vagos, Dell'Aglio, & Rijo, 2020, which evaluates the 18 maladaptive initial schemas, based on the model proposed by Schema-Focused Therapy, using 52 items presented in a non-consecutive way which are answered based on a six-point Likert scale. The mean responses to the items assessing each of the 18 EMSs are taken as an indicator of the salience of each of these EMSs themselves.…”
supporting
confidence: 53%
“…Regarding the Portuguese translation, most of the items were translated directly, although five items were adapted to better understand Brazilian adolescents. The Alpha for the violence suffered was 0.87 and the violence perpetrated was 0.88. proposed factors (Santos et al, 2018). In this study, the internal consistency of 14 out of 18 EMSs showed between 0.60 and 0.83, revealing an acceptable trustworthiness.…”
Section: Methodsmentioning
confidence: 55%
“…Fit indices derived from factor analysis models have been proposed as tools to estimate latent dimensions in multivariate data (Santos, Vagos, & Rijo, 2018;Schermelleh-Engel, Moosbrugger, & Müller, 2003;Ventimiglia & MacDonald, 2012). These fit indices include (among others): CFI (Bentler, 1990), TLI (Tucker & Lewis, 1973), RMSEA (Steiger, 1980), and SRMR (Joreskog & Sorbom, 1981).…”
Section: Fit Indices Used In Dimensionality Assessmentmentioning
confidence: 99%
“…The Portuguese-Brazilian version of the Schema Questionnaire for Adolescents (QEA) 36,37 : which evaluates the 18 early maladaptive schemas, using 52 items, presented non-consecutively, on a six-point Likert scale (1 = It has nothing to do with what happens to me to 6 = That's exactly what happens to me). The total score of each EMS is calculated by the mean of the sum of the items underlying the schema in question.…”
Section: Instrumentsmentioning
confidence: 99%